A flexible route to crisp-like metal–organic framework derivatives by crystalline transformation. Issue 23 (21st October 2022) - Li, Hongfeng; Ji, Ning; Ji, Xingyue; Liu, Shangjie; Shen, Yu; Pan, Ting; Wu, Peng; Hui, Junfeng; Zha, Baoli; Zhang, Weina
Abstract : Crisp-like MOF derivatives were fabricated by using MOF particles as precursors via the crystalline transformation process and sulfidation reactions. Abstract : Flexible design is one of the most significant features of metal–organic frameworks (MOFs) in that it can improve the efficiency of MOFs in storage, separation, sensing, and other applications. Herein, we reported a facile strategy to perform the flexible crystalline transformation of MOF polyhedra into their crisp-like derivatives. A mild hydrothermal process involved a crystalline change from ZIF-7 to Zn2 (bim)4 and a morphological change from an individual polyhedron to a string of nanosheets. Based on the crisp-like morphology which possessed abundant accessible active sites, composites such as Zn2 (bim)4 @ZnS and Zn2 (bim)4 @CoS could be obtained by further sulfidation and applied in oxygen evolution reactions (OERs) with a lower overpotential (330 mV) and good stability compared with a commercial IrO2 electrode. The well-organized Zn2 (bim)4 nanosheets with crisp-like morphology demonstrate an interesting crystalline transformation route to construct complicated nanostructures which are hardly achievable by direct synthesis, showing great promise for designing functional derived materials from MOFs.